(untitled) (Rivista italiana di Paleontologia e Stratigrafia, 2010)
The problems around the Pragian/Emsian (P/E) boundary have been widely discussed by several authors, who have pointed out that the present Global Stratotype Section and Point (GSSP) in the Zinzilban section (Kitab Reserve, Uzbekistan), is much older than the traditional German Siegenian-Emsian boundary, a fact that considerably reduces the duration of the traditional Pragian Stage. A comprehensive conodont study of two important sections (Isábena 1 and Baliera 6) demonstrates the presence of the conodont indexes for the P/E boundary in both senses (official and traditional) in the Spanish Central Pyrenees (SCP). Within the important conodont faunas registered, the presence of a new early polygnathid species Polygnathus rosae n. sp. stands out. Its stratigraphic range in the two sections is restricted to a short interval around the traditional beginning of the Emsian Stage. This particular distribution permits direct relation between both indexes, a better characterization of the P/E boundary in the traditional German sense and increases the palaeontological knowledge of this stratigraphic interval. Conodont records in the SCP suggest that Po. rosae n. sp. could be a good local index, too. In addition, Po. rosae n. sp. represents the last known step of the lineage Po. pireneaePo. rosae n. sp., a new early polygnathid lineage that supports the early radiation of the genus around the P/E boundary.